CD4+ T cells in chronic autoantigenic stimulation in MGUS, multiple myeloma and Waldenström's macroglobulinemia. Issue 5 (26th February 2015) - Neumann, Frank; Pfreundschuh, Michael; Preuss, Klaus D.; Schormann, Claudia; Zwick, Carsten; Murawski, Niels; Kubuschok, Boris
<x xml:space="preserve">Abstract</x> Hyperphosphorylated paratarg‐7 (pP‐7) carrier state is the strongest and most frequent molecular risk factor for MGUS, multiple myeloma (MM) and Waldenström's macroglobulinemia (WM), inherited autosomal‐dominantly and, depending on the ethnic background, found in up to one third of patients with MGUS/MM. Since P‐7 is the antigenic target of paraproteins that do not distinguish between wtP‐7 and pP‐7, we investigated CD4+ T‐cell responses in pP‐7+ patients and controls. Peptides spanning amino acids 1–35 or 4–31 containing phosphorylated or nonphosphorylated serine17 were used for stimulation. CD4+ cells from 9/14 patients (65%) showed a pP‐7 specific HLA‐DR restricted response. These results demonstrate that pP‐7 specific CD4+ cells can mediate help for pP‐7 specific chronic antigenic stimulation of P‐7 specific B cells, which might ultimately result in the clonal evolution of a B cell into MGUS/MM/WM producing a P‐7 specific paraprotein. Prerequisites for pP‐7 specific stimulation of CD4+ cells appear to be both a pP‐7 carrier state and an HLA‐DR subtype able to present and recognize pP‐7. Our results serve as an explanation for the exclusive autoimmunogenicity of the hyperphosphorylated variant of P‐7 and for the different hazard ratios of pP‐7 carriers from different ethnic origins to develop MGUS/MM/WM.